Pentingnya Penguatan Kinerja Keuangan, Pemanfaatan Teknologi Informasi, dan System Informasi Untuk Menilai Kualitas Laporan Keuangan - Helda Arta Melvia; Detak Prapanca; Vera Firdaus (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of financial performance, information technology utilization, and accounting information systems on the quality of financial reports at PT Sakti Mobile. The study used a quantitative approach with a purposive sampling technique on 70 respondents. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that the utilization of information technology and accounting information systems had a positive and significant effect on the quality of financial reports. Conversely, financial performance had a positive but insignificant effect. The coefficient of determination value of 0.620 indicates that the independent variables were able to explain 62% of the variation in the quality of financial reports, while other factors outside the research model influenced the remaining variables. These findings confirm that the effective use of information technology and integrated accounting information systems play a significant role in improving the relevance, reporting, comparability, and understandability of financial reports. This study provides practical implications for companies to strengthen the utilization of technology and information systems as an effort to improve the quality of financial reporting and support more accurate decision-making.